Bioethics and the thorny question of diversity: The example of Qatar-based institutions hosting the World Congress of Bioethics 2024 - Ghaly, Mohammed (Bioethics, 2023)
In 2022, the Research Center for Islamic Legislation & Ethics (CILE) and the World Innovation Summit for Health (WISH) submitted a proposal to host the 17th edition of the World Congress of Bioethics. After announcing that the CILE-WISH proposal was the winning bid, concerns were raised by bioethicists based in Europe and the USA. To address these concerns, the International Association of Bioethics (IAB) developed a dedicated FAQ section, in coordination with the host institutions, for the first time in IAB history. One-to-one communication ensued and individual responses were shared with these colleagues. As a continuation of this conversation, we (CILE Acting Director, WISH Research Fellow and Head of Content, and WISH CEO) address the concerns raised in the Letter-to-the-Editor of Bioethics by Graaf et al. As we support the call to revisit some contentious issues within the global community of bioethicists, we maintain that this should be based on meticulously discussed, informed, consistent and equitable criteria. We also argue that mutual learning from diverse cultures and moral traditions is the optimal way for our scholarly community to be truly global and to eschew the flaws ensuing from ethnocentric discourses.